Birth preparedness and complication readiness among women and couples and its association with skilled birth attendance in rural Bangladesh. - Sajia Islam; Janet Perkins; Md Abu Bakkar Siddique; Tapas Mazumder; Mohammad Rifat Haider; Mohammad Masudur Rahman; Cecilia Capello; Dewan Md Emdadul Hoque; Carlo Santarelli; Shams El Arifeen; Ahmed Ehsanur Rahman (PLoS ONE)
Introduction Despite remarkable progress in maternal and neonatal health over past two decades, maternal and neonatal mortality in Bangladesh remain high, which is partially attributable to low use of skilled maternal and newborn health (MNH) services. Birth preparedness and complications readiness (BCPR) is recommended by the World Health Organization and by the Government of Bangladesh as a key intervention to increasing appropriate MNH services. This study aims to explore the status of BPCR in a hard-to-reach area of rural Bangladesh and to demonstrate how BPCR practices is associated with birth in the presence of a skilled birth attendant. Methods Data was collected using multistage cluster sampling-based household survey in two sub-districts of Netrokona, Bangladesh in 2014. Interviews were conducted among women with a recent birth history in 12-months and their husbands. Univariate, bivariate, and multivariable analysis using Stata 14.0 were performed from 317 couples. Results Mean age of respondents was 26.1 (SD ± 5.3) years. There was a significant difference in BPCR practice between women and couples for identification of the place of birth (84% vs. 75%), identification of a birth attendant (89% vs.72%), arranging transport for birth or emergencies (20% vs. 13%), and identification of a blood donor (15% vs. 8%). In multivariable analysis, odds of giving birth in presence of a skilled birth attendant consistently increased with higher completeness of preparedness (OR 3.3 for 3-5 BPCR components, OR 5.5 for 4-5 BPCR components, OR 10.4 for all 5 BPCR components). For different levels of completeness of BPCR practice, the adjusted odds ratios were higher for couple preparedness comparatively. Conclusions BPCR is associated with birth in the presence of a skilled attendant and this effect is magnified when planning is carried out by the couple. Interventions aiming to increase BPCR practices should not focus on women only, as involving the couple is most likely lead to positive care-seeking practices.